Practices in sustainable industrial infrastructure and technology: A case study of Gujarat, India - Abhishek, Kumar; Biswas, Arindam (International Journal of Engineering and Technology, 2018)
Sustainable industrialisation is one of the seventeen Sustainable Development Goals formulated by the United Nations. It has a crucial role to play in achieving sustainability, because it is the driving mechanism for development of a countryâ€™s economy and instrumental to several environmental and social problems. For a developing country like India, it can ensure development in the right direction. Gujarat is one of the most industrialised states in India with high economic returns from the industrial systems but high levels of pollution as well. Some of the most polluted industrial towns in India and the world have been listed from Gujarat. For the past few decades, practices in sustainable industrial infrastructure have been playing a vital role in providing innovative solutions to complicated environmental problems, globally. Gujarat has been a leading State in India to promote these initiatives. The research paper intends to study and understand the direction of sustainable industrial development in Gujarat and presents the SWOT analysis of the existing situation. It includes case discussion of various cleaner production techniques, eco-efficiency and waste management practices.Â Â Â